HEAVY METAL CONTENT IN SOME SEAFOODS COLLECTED FROM MUARA ANGKE FISH AUCTION PLACE, JAKARTA. - Hutagalung, Horas; Syamsu, Suwirma (Marine Research in Indonesia, 1987)
Determination of  heavy  metal  content  (Hg, Pb, Cd, Cu, Cr, Zn) in some seafoods collected from  Muara  Angke  Fish  Auction  Place  were carried out during February to July 1979. The results showed  that Zn  content  in seafoods a nalyzed  was always much higher than the other heavy metals. The concentration levels of  the  six  heavy  metals observed were low. It is almost of the same level as the metal concentration of  other  seafoods  observed  in various parts of the world oceans, but still lower  than the maximum standard set  for human  consumption  as  established  by   Tasmania, Australia and  World Health Organization. The  mean  per capita  consumption of  fish  in Jakarta is only  about 165 g  per week, while  the  Provisional Tolerated Weekly Intake for Hg, set by WHO/FAO at 300 ug level, would be attained by consuming 1500 g Rastrelliger sp., or 698 gPenaeus setiferus, or 545 g Sepia sp., and or 1250 g Pecten sp.  Therefore,  at   present the  level of metal content in fishes sold at TPI  Muara  Angke  can be  considered  as  not  dangerous  to human health as long as these quantities are not surpassed.